Exact parallel plurality voting algorithm for totally ordered object space fault-tolerant systems - Karimi, Abbas; Zarafshan, Faraneh; Jantan, Adznan; Ramli, Abdul Rahman; Saripan, M. Iqbal; Syed Mohamed, Syed Abdul Rahman Al-Haddad (Universiti Putra Malaysia Press, 2012)
Plurality voter is one of the commonest voting methods for decision making in highly-reliable applications in which the reliability and safety of the system is critical. To resolve the problem associated with sequential plurality voter in dealing with large number of inputs, this paper introduces a new generation of plurality voter based on parallel algorithms. Since parallel algorithms normally have high processing speed and are especially appropriate for large scale systems, they are therefore used to achieve a new parallel plurality voting algorithm by using (n/log n) processors on EREW shared-memory PRAM. The asymptotic analysis of the new proposed algorithm has demonstrated that it has a time complexity of O (log n) which is less than time complexity of sequential plurality algorithm, i.e. Ω (n log n).